Security in Wireless LAN Attacks and Countermeasures - Rahmalia Syahputri; Muhammad Said Hasibuan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
Wireless LANs offer many advantages in its utilization. Flexibility, mobility, and can be implemented by individuals or industries, are a little example from that. Since the security standards SSID, WEP and MAC address filtering that implemented in 802.11 known has vulnerabilities, security is become the major weakness of wireless LANs. Masquerading, man-in-the middle attack, and denial of service are examples of attack which can happen in wireless LANs. New security standards are now under development and will be implemented in the new wireless LANs 802.11i, namely TKIP and AES. Booth these new standards are expected to cover the security hole. This report analysing various attacks in wireless LANs which are caused by the vulnerabilities of security features, and the possibility of countermeasures from the attacks.Keywords: wireless LANs, security, WEP, MAC address, authentication, attack, TKIP, AES.